(untitled) - Windsor, Philip (Boulder, Co., 2002)
This debate-style reader is designed to introduce students to controversies in justice and law through readings that reflect a variety of viewpoints. Each issue is framed with an issue summary, an issue introduction, and a postscript. The Taking Sides readers feature annotated listings of selected World Wide Web sites. Taking Sides is supported by our student website, Dushkin Online
Keywords: Nuclear warfare,Strategy,Cold War,Năng lượng hạt nhân,Chiến lược phát triển năng lượng